PROSPECTS FOR THE USE OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN MEDICAL SERVICES RELATED TO THE IMPLEMENTATION OF PATIENT RIGHTS (Scientific journal of the Fergana State University, 2023)
In the context of the globalization of the world economy and the development of technologies, it becomes a reality that the development of the national economy is impossible without the development of the digital economy. This, in turn, requires addressing the issue of widespread introduction of information technology in social life. That's why this article presents scientific and theoretical conclusions on the mechanisms for using digital technologies and artificial intelligence in medical services related to the realization of patients' rights.